Pengaruh Perilaku Kerja Inovatif dan Manajemen Pengetahuan terhadap Kinerja Organisasi pada Usaha Mikro dan Kecil - Helena Yosa Sundara; Agus Gunawan; Yoke Pribadi Kornarius; Angela Caroline (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2023)
Micro and Small Enterprises in the food and beverage industry contribute significantly to Indonesia’s economic growth. Micro and small businesses rely heavily on innovation to survive in the face of increasing competition. This study aims to determine and analyze the effect of innovative work behavior and knowledge management on the organizational performance of Micro and Small Enterprises (MSEs) in Bandung.  The study sample, consisting of 34 employees, was selected from six food and beverage businesses. Data processing results show that innovative work behavior and knowledge management do not affect organizational performance at micro and small enterprises. However, it was found that employee age plays a role in innovative work behavior and knowledge management.